WAS THE GOLD STANDARD REALLY DESTABILIZING?. (20th February 2012) - Fagan, Gabriel; Lothian, James R.; Mcnelis, Paul D.
SUMMARY This paper investigates the extent to which the high macroeconomic volatility experienced in the classical Gold Standard era of US history can be attributed to the monetary policy regime per se as distinct from other shocks. For this purpose, we estimate a small dynamic stochastic general equilibrium model for the classical Gold Standard era. We use this model to conduct a counterfactual experiment to assess whether a monetary policy conducted on the basis of a Taylor rule characterizing the Great Moderation data would have led to different outcomes for macroeconomic volatility and welfare in the Gold Standard era. The counterfactual Taylor rule significantly reduces inflation volatility, but at the cost of higher real‐money and interest‐rate volatility. Output volatility is very similar. The end result is no welfare improvement. Copyright © 2012 John Wiley & Sons, Ltd.